2018
DOI: 10.1007/s13760-018-1013-x
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune encephalitis and immune therapy: lessons from Argentina

Abstract: Autoimmune encephalitis (AE) is a common cause of noninfectious acute encephalitis. We aimed to provide the first review of immune therapy regimens used for patients with AE in Latin America, as well as the safety and efficacy associated with them, by reviewing the medical records of Argentine patients with AE treated between 2013 and 2018. Data included clinical symptoms, laboratory tests, electroencephalography, magnetic resonance imaging, cerebral spinal fluid, and neoplasm screenings. We examined ten AE pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In a cohort of Chinese patients, relapses were also uncommon, occurring in 7/86 (8.1%) AE patients, mainly affecting NMDAR patients (5/72, 6.9% of anti-NMDAR patients) (12). However, in a cohort of Argentine AE patients 25% of anti-NMDAR patients had relapses, but relapses also occurred in 25% of anti-LGI1 patients (15). Majority of the patients received firstline immunotherapy, steroid solely, or in combination with intravenous immunoglobulin or plasmapheresis, which had a good curative effect in most AE patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a cohort of Chinese patients, relapses were also uncommon, occurring in 7/86 (8.1%) AE patients, mainly affecting NMDAR patients (5/72, 6.9% of anti-NMDAR patients) (12). However, in a cohort of Argentine AE patients 25% of anti-NMDAR patients had relapses, but relapses also occurred in 25% of anti-LGI1 patients (15). Majority of the patients received firstline immunotherapy, steroid solely, or in combination with intravenous immunoglobulin or plasmapheresis, which had a good curative effect in most AE patients.…”
Section: Discussionmentioning
confidence: 94%
“…Complete recovery was assessed in AE patients with mRS score of 0 at the last visit following treatment (median: 33 months; range: 1-77) (12). Relapse was defined as the new onset or worsening of symptoms, after at least 2 months of improvement or stabilization (15).…”
Section: Data Collection and Analysesmentioning
confidence: 99%
“…The cure rate of AE was defined as the proportion of patients with mRS of 0 at the longest follow-up after treatment. Relapse of AE was defined as new onset or worsening of symptoms, occurring after at least 2 months of improvement or stabilization (8).…”
Section: Methodsmentioning
confidence: 99%
“…The modified ranking scale (mRS) score at last documented follow-up assessment was reported for 43 patients in 4 studies. Of those, 23 patients had an mRS score of 0, 12 patients had an mRS score of 1, two patients had an mRS score of 2, three patients had an mRS score of 3, two patients had an mRS score of 4, and one patient had an mRS score of 6 (3,(5)(6)(7)). An mRS ≤ 2 has been achieved in 86% of patients.…”
Section: Resultsmentioning
confidence: 99%
“…According to four studies included in this review, which add up to 43 patients, scores on the modified ranking scale (mRs) at the last evaluation during follow-up revealed that what has been considered as a "good outcome" (mRs ≤ 2) in previous reports has been achieved in the majority of patients (N = 37; 86.05%) (3,(5)(6)(7). This is consistent with larger data from international literature where an mRs ≤ 2 was achieved in 78.64% of patients (18).…”
Section: Discussionmentioning
confidence: 99%